2016
DOI: 10.1186/s40064-016-1967-1
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and hydroquinone content of skin toning creams and cosmetic soaps, and the potential risks to the health of Ghanaian women

Abstract: In this study, sixty-two (62) skin-lightening creams and soaps were analysed for total mercury and hydroquinone levels. Total mercury was determined by the Cold Vapour Atomic Absorption Spectrophotometry using an automatic mercury analyser and hydroquinone by High Performance Liquid Chromatography. The mean concentration of total mercury in skin toning creams and cosmetic soaps were 0.098 ± 0.082 and 0.152 ± 0.126 μg/g, respectively. The mean concentration of hydroquinone was 0.243 ± 0.385 and 0.035 ± 0.021 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 11 publications
2
36
2
Order By: Relevance
“…The present finding corroborates growing reports of the availability and use of high mercury‐containing bleaching agents . This trend is worrisome considering harms associated with the use of such agents including mercury poisoning, renal dysfunction, and neurological disorders . We also found that a large proportion of skin bleachers (32.7%) resort to the use of other substances including acids, caustics, herbal derivatives, and products of unknown composition with potentially dangerous consequences.…”
Section: Discussionsupporting
confidence: 89%
“…The present finding corroborates growing reports of the availability and use of high mercury‐containing bleaching agents . This trend is worrisome considering harms associated with the use of such agents including mercury poisoning, renal dysfunction, and neurological disorders . We also found that a large proportion of skin bleachers (32.7%) resort to the use of other substances including acids, caustics, herbal derivatives, and products of unknown composition with potentially dangerous consequences.…”
Section: Discussionsupporting
confidence: 89%
“…Assessment of the previous literature work has revealed that several societies across the world appreciate light skin as a form of beauty standard, whereas some regard it as a form of social capital (January et al, 2018). Agorku et al (2016) research on Ghanaian women showed that use of the skin whitening product led to an increase in skin-related disease. In the same context, Kouotou et al (2017) study on four university campuses of Yaoundé demonstrated that use of skin whitening products progresses due to the desire to have a uniform body skin color, following the desire for soft skin.…”
Section: Introductionmentioning
confidence: 99%
“…For the facial cream sample, the concentration of HQ was 2.60 μmol L −1 and CT was 3.03 μmol L −1 (Table ). Such concentrations were below the US FDA threshold limit about 2 % for dihydroxybenzenes , and the recoveries were in the range of 74.2–89.5 %. The RSD for all samples were below 1.6 %, evincing the selective simultaneous determination of HQ and CT in such “real‐world” complex samples.…”
Section: Resultsmentioning
confidence: 99%